Analisis Ukuran Butiran Pasir Menggunakan Teknik Pengolahan Citra Digital Metode Biner - Fitriyanti, Fitriyanti; Rayhani, Fathia; Ikhsan, Khaerul (SAINFIS: Jurnal Sains Fisika, 2025)
To determine a particle size, various methods are commonly used, including sieve analysis, laser diffraction sedimentation (LAS), electronical zone sensing (EZS), image analysis or microscopy, chromatography methods, and others. In some techniques, complex processes are typically required and analysis can be time-consuming. One method that simplifies particle size analysis, especially in the micro-size range, is by utilizing digital images. One of the methods in digital imaging is the binary method. Measurements using ImageJ software were conducted with two samples, namely beach sand and concrete sand, which have different particle sizes. Based on the research results, it was obtained that were in accordance with standard measurements based on references. For beach sand with a dataset of 57 samples, the range of particle size values obtained was 0.00220 – 0.766 mm, while for concrete sand with 56 data points, the minimum value obtained was 0.315, and the maximum value was 3.30.